The Impact of Work Family Conflict on Psychological Well-being of Woman Workers with Families in The Directorate General of Horticulture, Ministry of Agriculture, Republic of Indonesia - Mira Rizki Wijayani; Amir Supriyanto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study was to determine the effect of work family conflict on the psychological well-being of female workers with families in the Directorate General of Horticulture of the Ministry of Agriculture of the Republic of Indonesia. The research method used is quantitative research method using psychological scale as the primary data source. The population in this study amounted to 170 female workers with a total sample of 119 female workers Directorate General of Horticulture Ministry of Agriculture of the Republic of Indonesia. The analysis tool used in this study is a simple linear regression analysis. The results of this study showed a significant and negative influence of work family conflict on psychological well-being , this is indicated by the value of significance level 0.000 < 0.05, where Ho is rejected and Ha is accepted..